Characterizing caregivers of youth at risk for substance use and caregiver engagement in the youth legal system: a mixed methods approach - Turner, Annie; Pederson, Casey A.; Salgado, Eduardo; Dir, Allyson; Adams, Zachary; Zapolski, Tamika; Hulvershorn, Leslie; Aalsma, Matthew C. (Frontiers in Health Services, 2025)
BackgroundIncreasing caregiver and family participation is a key feature underlying many strategies to improve success among youth on community supervision. However, engaging caregivers in probation services remains a challenge for juvenile probation officers (JPOs), especially in families with significant needs. The goal of this study was to gain a better understanding of caregivers of legally involved youth at risk for substance use and their engagement with the youth legal system from a legal staff perspective.MethodsIn this mixed-methods study, qualitative interviews were conducted with n = 15 youth legal staff from two midwestern counties. In addition, surveys were analyzed from n = 72 caregivers of youth with recent legal involvement who were also at risk for substance use in the two counties to characterize caregivers and provide context to the staff interviews.ResultsQualitative themes identified from the staff interviews included defining caregiver engagement, barriers to caregiver engagement (e.g., financial barriers, transportation barriers, caregiver substance use, and lack of parenting skills), and strategies to increase caregiver engagement. Quantitative data from the caregiver surveys focused on demographics and life circumstances of caregivers in the counties studied.ConclusionsResults highlight a wide variability in degree of caregiver participation with the youth legal system and legal staff's approaches to caregivers as well as significant barriers that caregivers face in their attempt to be involved in their youth's lives and legal cases. Additional work is needed to explore the caregiver perspective and identify the impact of specific caregiver characteristics on their youth and their youth's legal outcomes.